An impact of thermal boundary conditions on characteristics of a non-Newtonian fluid flowing through a sudden pipe contraction - Ryltseva, K. E. (Thermophysics and aeromechanics)
A physical-mathematical model of a laminar axisymmetric flow of a power-law fluid through a sudden pipe contraction under non-isothermal conditions is presented with allowance for dissipative effects. The rheology of the liquid medium is determined by the Ostwald - de Waele law. The apparent viscosity is specified as a temperature-dependent function. Two options for setting the temperature boundary conditions on a solid wall are considered: the first implies invariable temperature along the pipe wall; and the second assumes a constant temperature value on the wall except for the area in the contraction plane vicinity, where the boundary is exposed to a zero-heat flux. The process is studied numerically using the finite-difference method. The main characteristics of the flow are calculated and visualized. The effect of thermal boundary conditions on the fluid flow structure and local pressure losses is analyzed.